Pengaruh Layanan Konseling Kelompok untuk Meningkatkan Rasa Kepercayaan Diri Siswa Kelas VIII-1 di Mts Proyek Kandepag - Putri, Auzha Amalia; Hasibuan, Uli Makmun; Aulia, Permata Dina; Riadi, Ali Akbar (Universitas Muhammadiyah Enrekang, 2024)
This study examines the problem of the effect of group counseling services with discussion techniques on the self-confidence of students in class VIII-1 at MTs Project Kandepag. Group counseling using discussion techniques is one of the effective ways to increase students self-confidence. This group counseling service was conducted in the classroom by Ali Akbar Riadi, Auzha Amalia Putri, and Permata Dina Aulia for 45 minutes. The results showed that group counseling services with discussion techniques were effective for increasing students' self-confidence, students who had low self-confidence experienced an increase in self-confidence after participating in group counseling services. This research shows that group counseling with discussion techniques can be an effective alternative to increase students' self-confidence